2021
DOI: 10.1016/j.celrep.2021.109076
|View full text |Cite
|
Sign up to set email alerts
|

Aging-dependent mitochondrial dysfunction mediated by ceramide signaling inhibits antitumor T cell response

Abstract: SUMMARY We lack a mechanistic understanding of aging-mediated changes in mitochondrial bioenergetics and lipid metabolism that affect T cell function. The bioactive sphingolipid ceramide, induced by aging stress, mediates mitophagy and cell death; however, the aging-related roles of ceramide metabolism in regulating T cell function remain unknown. Here, we show that activated T cells isolated from aging mice have elevated C14/C16 ceramide accumulation in mitochondria, generated by ceramide synthase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 93 publications
0
23
0
Order By: Relevance
“…This decline was reversed by treatment with (R)-α-lipoic acid (LA), a potent anti-oxidant/anti-inflammatory agent which reduced ceramide levels of aged mitochondria to a level comparable with young mitochondria ( Monette et al, 2011 ). Furthermore, it was recently discovered that mitochondrial dysfunction as a result of age-associated ceramide accumulation is induced partly through the inhibition of PKA, leading to the activation of mitochondrial fission factor, dynamin-related protein 1 (Drp1), and ultimately mitophagy ( Vaena et al, 2021 ).…”
Section: Sphingolipids and Other Hallmarks Of Agingmentioning
confidence: 99%
“…This decline was reversed by treatment with (R)-α-lipoic acid (LA), a potent anti-oxidant/anti-inflammatory agent which reduced ceramide levels of aged mitochondria to a level comparable with young mitochondria ( Monette et al, 2011 ). Furthermore, it was recently discovered that mitochondrial dysfunction as a result of age-associated ceramide accumulation is induced partly through the inhibition of PKA, leading to the activation of mitochondrial fission factor, dynamin-related protein 1 (Drp1), and ultimately mitophagy ( Vaena et al, 2021 ).…”
Section: Sphingolipids and Other Hallmarks Of Agingmentioning
confidence: 99%
“…It should be noted that most organisms have more than one CerS with distinct substrate specificity, resulting in diversity at the side-chain fatty acid level. This variety is critical for sphingolipiddependent signaling, since numerous studies have demonstrated different roles of acyl chain-specific sphingolipids in a variety of biological processes, including aging (7,(16)(17)(18).…”
Section: Sphingolipid Metabolism and Diversitymentioning
confidence: 99%
“…Cer and other sphingolipid metabolites have been shown to act directly on mitochondria. Certain Cer species, such as CerS-generated C14/C16 Cer, impair mitochondrial dynamics and function by promoting mitochondrial fragmentation or mitophagy, resulting in a series of aging-related disorders (16,18,97). In addition, Cer can directly bind to the mitochondrial anion channel voltage-dependent anion channel 2 and induce mitochondrial apoptosis (98).…”
Section: Lysosome-mitochondria Communication Mediates Sphingolipid Ef...mentioning
confidence: 99%
“…In line with this, the impairment of mitochondrial function in activated CD8 + T cells is sufficient to suppress proliferation and upregulate genes linked to the exhaustion of T cells ( 106 ). Besides, the dysfunction of the mitochondria is also responsible for the deficiency of the antitumor immunity of T cells during the process of aging, indicating that the mitochondria can build the bridge between aging and its related tumor immunology ( 107 ). Furthermore, those tumor-reactive effector/memory cytotoxic T lymphocytes in draining lymph nodes are characterized with increased PGC-1α expression as well as concomitant mitochondrial OXPHOS activation, forwardly indicating the facilitative role of OXPHOS in the antitumor function of T cells ( 108 ).…”
Section: Mitochondrial Oxidative Phosphorylation In Melanoma Immunologymentioning
confidence: 99%